2017
DOI: 10.1111/den.12909
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic treatment of pancreatic duct stones under direct vision: Revolution or resignation? Systematic review

Abstract: Background and Aim: The main treatment aim in chronic pancreatitis (CP) is symptom control and especially pain relief. Management of stone-predominant CP is challenging and requires a multidisciplinary approach. Extracorporeal shock wave lithotripsy (ESWL) has emerged as the cornerstone of nonsurgical treatment as a result of disappointing results of available endoscopic treatment options during the last decades. With new developments in the field of direct peroral pancreatoscopy (POP) and intracorporeal litho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
50
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(53 citation statements)
references
References 36 publications
3
50
0
Order By: Relevance
“…Due to the small cohort, no definite answer can be provided as to whether laser lithotripsy or EHL is more effective. However, it is in line with reported PEP rates in average high-risk ERCP patients of 20.2 % to 40 % [14 -15] and in SOVP patients with PEP up to 28 % [2,4,6]. Risk factors include patient-, physician-or procedure-related and are additive [14].…”
Section: Discussionsupporting
confidence: 87%
“…Due to the small cohort, no definite answer can be provided as to whether laser lithotripsy or EHL is more effective. However, it is in line with reported PEP rates in average high-risk ERCP patients of 20.2 % to 40 % [14 -15] and in SOVP patients with PEP up to 28 % [2,4,6]. Risk factors include patient-, physician-or procedure-related and are additive [14].…”
Section: Discussionsupporting
confidence: 87%
“…Intraductal lithotripsy techniques, including laser lithotripsy (LL) and electrohydraulic lithotripsy (EHL), can be attempted either after failure of ESWL or before in an experimental setting. Literature on these lithotripsy techniques in PD stones is scarce, with only one systematic review published showing complete ductal clearance in 43-100 % and adverse events in 0 % to 13.5 % [45]. Large, prospective studies are needed to prove efficiency and safety of these techniques and to compare outcomes with ESWL.…”
Section: Original Articlementioning
confidence: 99%
“…Howell et al [82] first described MPD stone removal under direct visualization using an electrohydraulic lithotripsy (EHL) probe in 1999. A systematic review from 2017 including 88 patients from 10 publications, among them 2 prospective studies, showed high treatment success rates with acceptable complication rates [83]: 5 studies used EHL, 4 studies used laser, 1 study used a basket for stone extraction, 1 study compared laser with EHL, and 1 study used a combination of ESWL first, followed by EHL during POP. The study in which ESWL had been performed before POP described an exceptionally low treatment success (43%) and the highest complication rate (28%) [84].…”
Section: Endoscopic Therapymentioning
confidence: 99%